Intermittent breeding and the dynamics of resource allocation to reproduction, growth and survival. (23rd November 2012) - Baron, Jean‐Pierre; Le, Jean‐François; Ferrière, Régis; Tully, Thomas; Herrel, Anthony
Summary In iteroparous organisms, the timing of reproduction varies greatly and reproduction may be intermittent. Here, we investigate the proximate determinants of intermittent breeding and their evolutionary significance in a viviparous snake, the meadow viper Vipera ursinii ursinii. We used individual life‐history data collected over a 28‐year capture–mark–recapture field study. Among viviparous snakes, the meadow viper's almost exclusively insectivorous diet is remarkable. Breeding females maintain substantial foraging activity during gestation. The life cycle is iteroparous, and female breeding frequency is essentially biennial. Breeding status is strongly associated with a threshold on female body condition prior to vitellogenesis. Non‐breeding females grow and store fat reserves needed for future reproduction. Breeding females convert reserves into eggs, the number of which is determined by maternal size and body condition prior to vitellogenesis. During pregnancy, females stop growing. Females survive breeding and non‐breeding years with equal probabilities. Our results suggest that income resources during pregnancy are used to fully cover the costs of gestation. Integration of our data into a matrix population model allowed us to relate breeding pattern to fitness. According to the model, biennial breeding is strongly favoured by natural selection if consecutive breeding decreases maternal survival and/or fecundity. Growth cessation during breeding years generates weak selection pressures for intermittent breeding.